Pemanfaatan Limbah Keraginan Rumput Laut Menjadi Plastik Biodegradable - Eginta Marovid Tarigan; Okik HendriyantoCahyonugroho (Jurnal Serambi Engineering, 2024)
This research aims to utilize seaweed craft waste as a basic material for biodegradable plastic by adding chitosan and sorbitol as plasticizers. Seaweed craft waste is extracted to obtain cellulose which is then mixed with chitosan and sorbitol in certain variations. The mechanical characteristics, biodegradation and water absorption capacity of the resulting biodegradable plastic were evaluated. The research results showed that the tensile strength of biodegradable plastic ranged from 1.68 to 2.41 MPa, elongation ranged from 6.9% to 20.9%, biodegradation test ranged from 63.5% to 66.53%, and water absorption capacity. ranges from 1.8% to 2.37%. Statistical correlation shows that the addition of chitosan tends to strengthen the mechanical properties and inhibit biodegradation and water absorption, while the addition of sorbitol tends to weaken the mechanical properties and increase the water absorption. The optimum conditions for biodegradable plastic vary depending on the parameters measured, and the characteristics of the plastic do not fully meet applicable standards. Nevertheless, this research provides an overview of the potential and limitationsof using seaweed craft waste for the production of biodegradable plastic.